2013
DOI: 10.1111/opec.12003
|View full text |Cite
|
Sign up to set email alerts
|

Empirical analysis of fuel price and subsidy reform in Nigeria

Abstract: Fuel subsidy removal has been a very topical and delicate issue in Nigeria. In spite of government assurance that the proceeds from the fuel subsidy withdrawal will be used judiciously and effectively to provide critical infrastructure that will cushion its effects, the opponents have remained resolute on their uncompromising stand against its removal. The goal of this study is to determine the actual size of fuel subsidy in Nigeria. It is therefore hypothesised that there was no significant relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Moreover, the energy subsidies in some oil-producing countries (including Nigeria) 9 have been criticised for their pervasive consequences, which include influencing households' energy consuming habits and lifestyle, and causing a deterioration in energy efficiency and consequently higher CO 2 emissions (see e.g. Fattouh and El-Katiri (2013); Nwachukwu et al (2013); Olivia and Gibson (2008)). Arguably, the effect of these dynamics (or factors) on energy demand and CO 2 emissions cannot be captured purely with energy price and income variables (or perhaps with a scenario analysis).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the energy subsidies in some oil-producing countries (including Nigeria) 9 have been criticised for their pervasive consequences, which include influencing households' energy consuming habits and lifestyle, and causing a deterioration in energy efficiency and consequently higher CO 2 emissions (see e.g. Fattouh and El-Katiri (2013); Nwachukwu et al (2013); Olivia and Gibson (2008)). Arguably, the effect of these dynamics (or factors) on energy demand and CO 2 emissions cannot be captured purely with energy price and income variables (or perhaps with a scenario analysis).…”
Section: Introductionmentioning
confidence: 99%
“…Government credibility is linked to a perception of the government's ability to implement reforms and redistribute or reinvest savings from reforms ( Beaton et al, 2013 ; Bridel and Lontoh, 2014 ; Baig et al, 2007 ; Indriyanto et al, 2013 ; Scobie, 2018 ). In the Nigerian context, some authors have suggested that there is a trust deficit ( Ogbu, 2012 ), with many reform opponents such as labour unions and civil right groups highlighting the inability of governments to protect the poor ( Soile and Mu, 2015 ; Bashir, 2013 ; Nwachukwu et al, 2013 ; Africa Research Bulletin, 2011 ; Akov, 2015 ).…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…4 Subsidies exist because the government fixes the price of petrol for consumers below the international price, and uses government resources to pay for the difference. 5 Despite numerous attempts at reform, Nigeria has never successfully removed petrol subsidies, 6 in large part because of strong popular opposition to reform; Nwachukwu et al (2013) as well as Akov (2015) have highlighted the large level of petrol subsidies and the coalition of interest groups that have cooperated to protect the continuation of subsidization.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless,Elum and Momodu (2017) argued that social and political bottlenecks are the significant impediments to a green Nigeria. Other studies on fuel subsidy discuss in Nigeria but are not explicitly examining the fuel subsidy induced carbon emission growth trajectories are acknowledged (seeAkanle, Adebayo and Adetayo (2014);Nwachukwu and Chike (2011);Nwachukwu, Mba, Jiburum and Okosun (2013);Siddig, Aguiar, Grethe, Minor and Walmsley (2014);Soile and Mu (2015) for an extensive review).…”
mentioning
confidence: 99%